(untitled) (Vietnam Journal of Community Medicine, 2025)
Abstract: The study aimed to evaluate the results after transurethral endoscopic resection of advanced prostate cancer with bilateral orchiectomy at Viet Duc Hospital from January 2018 to December 2022. Subjects and methods: The retrospective method followed up longitudinally on 217 patients diagnosed with advanced prostate cancer who underwent transurethral resection of the tumor with bilateral orchiectomy. Results: Most of the patients were in stages T3, T4 accounting for 82.9%, early stage T2 accounting for only 17.1%. Of the 217 patients, 118 were alive (54.4%), 99 patients (45.6%) died. The survival rate decreased gradually over the follow-up time of the groups from 24 to 72 months after surgery, corresponding to 67.1% to 36.8%. The main cause of death was cancer metastasis to other organs. Factors affecting survival rate and overall survival time were Gleason score, age group and stage of Prostate cancer (p<0.05). The ability to urinate and the quality of life of patients improved significantly after surgery: according to the IPSS scale, the majority of postoperative patients at the time of re-examination - interview had mild and moderate urinary disorders, accounting for 94.1%, much higher than the pre-operative level of 36.5% (p<0.001). The quality of life (QoL) of postoperative patients was at an acceptable and satisfactory level of 90.6%, higher than the pre-operative level of 18.5% (p<0.001).